Pendidikan Islam, Civil Society Dan Problem Standarisasi Mutu - Mutmainah Mutmainah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2016)
Civil society, in the perspective of education (Islamic education), is a great subject owned by Islamic education in educational empowerment of the people as a whole. With its proximity to the Muslim community, Islamic education is a subject in the formation of civil society at the grassroots of Muslims. Civil society, in the perspective of Islamic education, is a significant topic that is actually owned by Islamic education in the empowerment of community education in a comprehensive manner. Islamic education, based on a community-based education, became one of the foundations in creating a civil society. Islamic education can be a vehicle for "critical pedagogy" (critical education), for the people; freeing the lowest layer of society from backwardness and poverty.